Investigation of Under-reporting of Occupational Accident in Turkey - Dalyan, Orkun; Canpolat, Erdal; Dalyan, Hatice; Öztürk, Ömer Faruk; Pişkin, Mehmet (Zonguldak Bülent Ecevit Üniversitesi, 2021)
In this study, a survey study consisting of 15 questions was organized for employees working in occupational health and safety units throughout Turkey to determine the under-reporting data in the occupational accident statistics published by the Social Security Institution between 2013 and 2019. Survey data answered by 331 employees were analyzed with the Statistical Program for Social Sciences 24.0. 275 (83%) of the participants have certificates in occupational safety and 56 (17%) in occupational health departments. According to the data obtained, it has been determined that the personnel between the ages of 18-28, associate degree graduates, 0-3 years of professional experience and C class occupational safety specialist certificate give more positive answers to the examination of occupational accident statistics deficiency in Turkey compared to other groups. With the applied survey, it was concluded that there was a significant difference at a very high effect level between the variables of age, education level, professional experience and certificate class. According to the results of the research, it is recommended that employers regularly receive training on occupational accidents and their reporting by authorized institutions and that occupational safety specialists-workplace physicians are actively involved in the occupational accident reporting process.

Bu çalışmada, Türkiye genelinde iş sağlığı ve güvenliği birimlerinde görevli personellere, Sosyal Güvenlik Kurumu’nun 2013-2019 yılları arasında yayımladığı iş kazası istatistiklerindeki eksik olduğu düşünülen verilerin tespiti amacıyla 15 sorudan oluşan bir anket çalışması düzenlenmiştir. 331 çalışan tarafından cevaplandırılan anket verileri Sosyal Bilimler için İstatistik Programı 24.0 ile analiz edilmiştir. Katılımcıların 275’i (%83) iş güvenliği, 56’sı (%17) iş sağlığı bölümlerinde sertifikaya sahiptir. Elde edilen verilere göre, 18-28 yaş arası, ön lisans mezunu, 0-3 yıl arası mesleki tecrübeye ve C sınıfı uzmanlık sertifikasına sahip personellerin diğer gruplara göre Türkiye'deki iş kazası istatistiklerinin irdelenmesine ilişkin daha olumlu cevaplar verdiği tespit edilmiştir. Uygulanan anket ile yaş, eğitim düzeyi, mesleki tecrübe ve sertifika sınıfı değişkenleri arasında çok yüksek etki düzeyde anlamlı farklılık olduğu sonucuna ulaşılmıştır. Araştırma sonuçlarına göre, işverenlerin iş kazaları ve raporlanması hakkında düzenli olarak yetkili kurumlar tarafından eğitim alması ve iş güvenliği uzmanı-işyeri hekimlerinin iş kazası raporlama sürecine aktif olarak dahil edilmesi önerilmektedir.
Türkiye’de İş Kazası Eksik Bildirimlerinin İncelenmesi